Pressed for All Time : Producing the Great Jazz Albums from Louis Armstrong and Billie Holiday to Miles Davis and Diana Krall - Jarrett, Michael, 1953- (Book collections on Project MUSE., 2016)
In histories of music and audio technologies, and particularly in narratives about jazz, record producers tend to fall by the wayside. They're seldom acknowledged and generally unknown. But without them and their contributions to the art form, we'd have little on record of some of the most important music ever created. This oral history-organizing interviews gathered by music scholar Michael Jarrett-tells the stories behind some of jazz's best-selling and most influential albums.